SOSIALISASI DAN PELATIHAN PEMBIBITAN MANGROVE PADA KAWASAN PESISIR PANTAI SEVAV RATUT DESA OHOIDERTOM KABUPATEN MALUKU TENGGARA - Melissa Renjaan; Maxthedora Rematwa; Yosua Tanlain (Politeknik Negeri Sriwijaya, 2022)
Based on the results of surveys and observations, high abrasion has been seen on the western coast of Kei Kecil Barat District, Southeast Maluku Regency as well as Sevav Hamlet, Ohoidertom Village. Geographically, the location of the village is directly opposite the open sea. therefore causing high wave pressure accompanied by strong winds to hit the coast throughout the west monsoon. This is caused by the loss of coastal vegetation due to community activities. Therefore, it is very important to take steps to rehabilitate the coastal area by involving the community and youth of Ohoidertom village. This community service activity includes socialization and training conducted in May 2021. The purpose of this activity is to educate the community about the benefits of mangroves for the coastal environment, then increase awareness of the mangrove ecosystem and to train the community to carry out coastal rehabilitation through mangrove cultivation. This community service activity uses interactive dialogue and training methods. The result of this socialization and training activity was an agreement from Sevav traditional leaders to implement the